Cardiomyocyte contractile force changes in response to AGRWE detected by AFM. (1st May 2019) - Qu, YingMin; Zhao, Feihu; Wang, Xinyue; Liu, Jinyun; Li, Jingmei; Song, Zhengxun; Wang, Zuobin
Abstract : The cardiac contractile force is an important predictor of healthy and cardiovascular diseases. The changes of cardiomyocyte contractile force in response to American ginseng root water extract (AGRWE) detected by atomic force microscope have not been investigated yet. This study examined the effects of AGRWE on single beating cardiomyocytes extracted from a newborn rat. The same cardiomyocytes were incubated with AGRWE at a concentration of 50 μg/ml for about 30 min, and the cardiomyocytes' contractile force increased from 1.74 ± 1.01 to 3.49 ± 1.53 nN. The mean value of the contractile strain calculated was 3.32 ± 1.55% for the cardiomyocyte before the treatment with AGRWE, while for the cardiomyocyte treated with AGRWE it increased to 4.60 ± 1.35%. The results also showed that the beating rate of the same single beating cardiomyocytes was decreased from 34 ± 11 beats/min (control, n = 10) to 20 ± 9 beats/min. In conclusion, the experimental results have shown clearly that the contractile forces and strain of single beating cardiomyocytes treated with AGRWE are significantly higher than the control group, while the heart rate was decreased. It suggests that ginseng agents are promising candidates in improving cardiac functions for treating heart failure.